2022
DOI: 10.1002/cjce.24358
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and water activity control in a lipase catalyzed esterification process using nonlinear model predictive control

Abstract: Controlling the batch esterification process is a difficult task because the kinetics of the process incorporate intrinsic nonlinearity, process uncertainty, and model mismatch. The model predictive control (MPC) was created and used in the lipase‐catalyzed esterification process in this study. The Autoregressive with Exogenous Input (ARX) and Nonlinear Autoregressive with Exogenous Input (NARX) models were embedded in the MPC. The controller's goal is to manipulate the jacket flow rate and air flow rate, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Lipases are frequently utilized in these types of reactions. The effect of water activity on the speed of reaction of lipases has been studied [ 170 ]. The results revealed that lipases from different sources react to an increase in water activity in different ways.…”
Section: Recent Trends and Targets In Lipase Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipases are frequently utilized in these types of reactions. The effect of water activity on the speed of reaction of lipases has been studied [ 170 ]. The results revealed that lipases from different sources react to an increase in water activity in different ways.…”
Section: Recent Trends and Targets In Lipase Engineeringmentioning
confidence: 99%
“…The lipases from Rhizopus arrhizus exhibit optimum activity at low levels of water activity, while lipases from the Pseudomonas species exhibit activity that increases with water activity. Lipases from Candida rugosa have intermediate profiles with broader maxima [ 170 , 171 ].…”
Section: Recent Trends and Targets In Lipase Engineeringmentioning
confidence: 99%